The Oxford Companion to Philosophy - Honderich, Ted (Oxford Oxford University Press, 1995)
Philosophy can be intriguing--and at times baffling. It deals with the central problems of the human condition--with important questions of free will, morality, life after death, the limits of logic and reason--though often in rather esoteric terms. Now, in The Oxford Companion to Philosophy, readers have the most authoritative and engaging one-volume reference work on philosophy available, offering clear and reliable guidance to the ideas of all notable philosophers from antiquity to the present day, and to the major philosophical systems around the globe, from Confucianism to phenomenology.Here is indeed a world of thought, with entries on idealism and empiricism, ethics and aesthetics, epicureanism and stoicism, deism and pantheism, liberalism and conservativism, logical positivism and existentialism--over two thousand entries in all. The contributors represent a veritable who's who of modern philosophy, including such eminent figures as Isaiah Berlin, Sissela Bok, Ronald Dworkin, John Searle, Michael Walzer, and W. V. Quine. We read Paul Feyerabend on the history of the philosophy of science, Peter Singer on Hegel, Anthony Kenny on Frege, and Anthony Quinton on philosophy itself. We meet the great thinkers--from Aristotle and Plato, to Augustine and Aquinas, to Descartes and Kant, to Nietzsche and Schopenhauer, right up to contemporary thinkers such as Richard Rorty, Jacques Derrida, Luce Iragaray, and Noam Chomsky (over 150 living philosophers are profiled). There are short entries on key concepts such as personal identity and the mind-body problem, major doctrines from utilitarianism to Marxism, schools of thought such as the Heidelberg School or the Vienna Circle, and contentious public issues such as abortion, capital punishment, and welfare. In addition, the book offers short explanations of philosophical terms (qualia, supervenience, iff), puzzles (the Achilles paradox, the prisoner's dilemma), and curiosities (the philosopher's stone, slime). Almost every entry is accompanied by suggestions for further reading, and the book includes both a chronological chart of the history of philosophy and a gallery of portraits of eighty eminent philosophers, from Pythagoras and Confucius to Rudolf Carnap and G.E. Moore. And finally, as in all Oxford Companions, the contributors also explore lighter or more curious aspects of the subject, such as "Deaths of Philosophers" (quite a few were executed, including Socrates, Boethius, Giordano Bruno, and Thomas More) or "Nothing so Absurd" (referring to Cicero's remark that "There is nothing so absurd but some philosopher has said it"). Thus the Companion is both informative and a pleasure to browse in, providing quick answers to any question, and much intriguing reading for a Sunday afternoon.An indispensable guide and a constant source of stimulation and enlightenment, The Oxford Companion to Philosophy with appeal to everyone interested in abstract thought, the eternal questions, and the foundations of human understanding.
Keywords: Philosophy